The determination of urinary amines by one-dimensional paper chromatography - Stott, A. W. (1966)
A method for the determination of urinary normetadrenaline and metadrenaline is described whereby these 3-O-methoxy metabolites of noradrenaline and adrenaline are separated by paper chromatography before estimation by Pisano's method. Results in 80 normal subjects are given.